Policy Implementation Regarding Tourism Sector Development Planning in Bappeda Pangandaran, West Java, Indonesia - Andre Ariesmansyah; Rifqi Khairul Arifin; Regan Vaughan; Mona Indrianie (GoResearch - Research & Publishing House, 2022)
Implementation of Policy Concerning Tourism Sector Development Planning at BAPPEDA Pangandaran This research which is used as a comparison in policy implementation is the theory of Ripley and Franklin (2007) namely Compliance, Smooth Routine Functions, Realization of Performance and Desired Impact. There was only one informant in this study, namely the Head of the Sub-Sector of Tourism, Industry, Trade and Investment. Based on the results of the study, the implementation of policies regarding tourism sector development planning at BAPPEDA Pangandaran Regency as a whole has been supportive and well implemented but not yet effective due to a lack of coordination and synchronization with each other. Adapting to technological advances can be a strong signal for making new policies in the future. Improving the quality of human resources for the actors of tourism management towards world-class tourism. Providing special training by intensifying the physical arrangement and the role of the performance of the employees must be able to improve the HR apparatus so that it is more